Influencing factors for sustainable design implementation in the front-end of new product development process within the Fast-Moving-Consumer-Goods sector - Park, Curie (Cranfield University, 2015)
This study examines and verifies the influencing factors for sustainable design implementation in the front-end stages of New Product Development (NPD) process within the Fast-Moving-Consumer-Goods (FMCG) sector. Despite many arguments that the early consideration of sustainable design is key to successful sustainable product development, there is a paucity of research that approaches sustainable design implementation from an NPD front-end perspective. Moreover, sustainable design research in the FMCG sector is rare in spite of the sector’s substantial impact to the environment and society. In order to gain holistic insights of the subject, this study explores different epistemic communities ranging from industrial sustainable design, engineering sustainable design, NPD front-end studies, to corporate social responsibility (CSR) studies. Subsequently, multiple FMCG case studies are conducted to confirm and elaborate the literature findings. Among a total of 11 factors and 32 elements of case studies findings, nine factors and 19 elements confirm the previous findings, and two factors and 13 elements are newly identified. Six confirming factors including senior management support, internal communication, cross-‐functional team, and supportive corporate culture are common sustainable design and NPD front-end factors. Three other confirming factors including sustainability tools, and sustainability champions are distinct sustainable design factors, and two new factors including balanced focus on growth and maturity of external contexts and seven elements are specific to the FMCG context. Also a disparity between the perception and practice of the factors is highlighted. More positive, frequent evidence of the factors is observed in higher sustainability maturity level companies. A conceptual framework is suggested to explain the interrelationships of factors. The research findings contribute to a holistic understanding of the nature of sustainable design implementation in the front-end of NPD for FMCG. The research is hoped to serve as guide for FMCG practitioners in diagnosing their sustainable design implementation within the NPD process, and developing more holistic sustainability strategy in a long-term view.